How do patients pass through stroke services? Identifying stroke care pathways using national audit data. (May 2020) - Gittins, Matthew; Lugo-Palacios, David G; Paley, Lizz; Bray, Benjamin; Bowen, Audrey; Vail, Andy; Gannon, Brenda; Tyson, Sarah
Objective: To map and describe how patients pass through stroke services. Methods: Data from 94, 905 stroke patients (July 2013–July 2015) who were still inpatients 72 hours after hospital admission were extracted from a national stroke register and were used to identify the routes patients took through hospital and community stroke services. We sought to categorize these routes through iterative consultations with clinical experts and to describe patient characteristics, therapy provision, outcomes and costs within each category. Results: We identified 874 routes defined by the type of admitting stroke team and subsequent transfer history. We consolidated these into nine distinct routes and further summarized these into three overlapping 'pathways' that accounted for 99% of the patients. These were direct discharge (44%), community rehabilitation (47%) and inpatient transfer (19%) with 12% of the patients receiving both inpatient transfer and community rehabilitation. Patients with the mildest and most severe strokes were more likely to follow the direct discharge pathway. Those perceived to need most therapy were more likely to follow the inpatient transfer pathway. Costs were lowest and mortality was highest for patients on the direct discharge pathway. Outcomes were best for patients on the community rehabilitation pathway and costs were highest where patients underwent inpatient transfers. Conclusion: Three overarching stroke care pathways were identified which differ according to patient characteristics, therapy needs and outcomes. This pathway mapping provides a benchmark to develop and plan clinical services, and for future research.